Functional Gene Identification and Corresponding Tolerant Mechanism of High Furfural-Tolerant Zymomonas mobilis Strain F211 - Hu, Dongsheng; Wang, Zhiquan; He, Mingxiong; Ma, Yuanyuan (Frontiers in Microbiology, 2021)
Furfural is a major inhibitor in lignocellulose hydrolysate for Zymomonas mobilis. A mutant F211 strain with high furfural tolerance was obtained from our previous study. Thus, its key tolerance mechanism was studied in the present study. The function of mutated genes in F211 was identified by functional complementation experiments, revealing that the improved furfural tolerance was resulted from the C493T mutation of the ZCP4_0270 gene promoting cell flocculation and the mutation (G1075A)/downregulation of ZCP4_0970. Comparative transcriptome analysis revealed 139 differentially expressed genes between F211 and the control, CP4, in response to furfural stress. In addition, the reliability of the RNA-Seq data was also confirmed. The potential tolerance mechanism was further demonstrated by functional identification of tolerant genes as follows: (I) Some upregulated or downregulated genes increase the levels of NAD(P)H, which is involved in the reduction of furfural to less-toxic furfuryl alcohol, thus accelerating the detoxification of furfural. (II) The mutated ZCP4_0270 and upregulated cellulose synthetase gene (ZCP4_0241 and ZCP4_0242) increased flocculation to resist furfural stress. (III) Upregulated molecular chaperone genes promote protein synthesis and repair stress-damaged proteins. (Ⅳ) Transporter genes ZCP4_1623–1625 and ZCP4_1702–1703 were downregulated, saving energy for cell growth. The furfural-tolerant mechanism and corresponding functional genes were revealed, which provides a theoretical basis for developing robust chassis strains for synthetic biology efforts.